2010
DOI: 10.1007/s11689-010-9059-y
|View full text |Cite
|
Sign up to set email alerts
|

Developmental malformation of the corpus callosum: a review of typical callosal development and examples of developmental disorders with callosal involvement

Abstract: This review provides an overview of the involvement of the corpus callosum (CC) in a variety of developmental disorders that are currently defined exclusively by genetics, developmental insult, and/or behavior. I begin with a general review of CC development, connectivity, and function, followed by discussion of the research methods typically utilized to study the callosum. The bulk of the review concentrates on specific developmental disorders, beginning with agenesis of the corpus callosum (AgCC)—the only co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
197
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(208 citation statements)
references
References 298 publications
(391 reference statements)
6
197
1
4
Order By: Relevance
“…45 In children with autism, a reduction in volumes of the CC has been reported, with a lack of the age-related positive correlation between age and CC volume. 18 Thus, our findings of the CC volumes are unlikely to be due to a non-specific finding associated with cognitive impairments.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…45 In children with autism, a reduction in volumes of the CC has been reported, with a lack of the age-related positive correlation between age and CC volume. 18 Thus, our findings of the CC volumes are unlikely to be due to a non-specific finding associated with cognitive impairments.…”
Section: Discussionmentioning
confidence: 63%
“…17 The fiber connections between corresponding hemispheric regions are topographically arranged; thus, structural changes in the CC are reflective of changes in the corresponding cortical areas. Diminished connectivity in the CC may be involved in the pathophysiology of many neurodevelopmental disorders 18 and schizophrenia. 19 We previously reported that the CC area was larger in children with 22q11DS, compared with typically developing children, 20 replicated by others.…”
Section: Introductionmentioning
confidence: 99%
“…The midbody of the corpus callosum is implicated in processing primary sensory and higher order auditory information along with premotor and primary motor cortices [54][55][56]. Large axons within the midbody of the corpus callosum facilitate rapid sensory integration essential to perceive temporal cues in auditory and visual stimuli which are needed for phonological processing and ultimately fluent reading.…”
Section: The Role Of the Corpus Callosum In Reading And Developmentalmentioning
confidence: 99%
“…In typical development, the splenium consists of small densely packed axons; thus, splenium enlargement suggests a greater number of axons and greater interhemispheric connectivity [56]. Furthermore, compared to typically developing adults (N=18), individuals with DD (N=9) display increased FA and AD in the splenium [49].…”
Section: The Role Of the Corpus Callosum In Reading And Developmentalmentioning
confidence: 99%
“…This condition occurs in 1:4000 individuals, which makes it one of the most common human brain malformations [7]. The etiology of ACC has an identifiable cause in about 25% of cases [7], and is usually related to other neurological conditions such as hydrocephalus [8], microcephaly [9], or fetal alcohol syndrome [10].…”
Section: Introductionmentioning
confidence: 99%